Crystal Structure, Antitumour and Antibacterial Activity of Imidazo[1, 2‐α]pyridine Ligand Containing Palladium Complexes. Issue 2 (16th January 2020) - Alam, Md N.; Yu, Jun Q.; Beale, Philip; Turner, Peter; Proschogo, Nick; Huq, Fazlul
Abstract: Due to similar coordination chemistry of palladium with platinum, a lot of palladium compounds investigated for their anticancer activity after the discovery of cisplatin. Imidazo[1, 2‐α]pyridine is a drug precursor scaffold and has already been successfully utilized to come up with a number of clinical drugs against various diseases. In this present study anticancer and antimicrobial activity of three palladium complexes e. g. [PdL4 ]2Cl (coded as NH4), PdL2 Cl2 (coded as NH5) and [PdL4 ]2Cl.(4H2 O).L (coded as NH6) where L=imidazo[1, 2‐α]pyridine ligand has been described. All of the synthesized palladium complexes have been characterized by elemental microanalysis and spectral techniques. [PdL4 ]2Cl and [PdL4 ]2Cl.(4H2 O).L were also characterized by single crystal X‐ray diffraction method. MTT reduction assay was used to determine the anticancer activity against three human ovarian tumour models and three colorectal tumour models. PdL2 Cl2 has shown moderate anticancer activity with lower resistance factor value against ovarian cancer model compared to clinical standard cisplatin. The same complex also exhibited significant antitumour activity in all colorectal tumour models. The rest of the complexes did not show significant anticancer activity but one of the complexes displayed promising antibacterial activity against Staphylococcus aureus . PdL2 Cl2 could act at least as a lead to develop new anticancer agent. Abstract : Three palladium complexes have been prepared using imidazo[1, 2‐α]pyridine ligand among which two of them characterized by single crystal X‐ray diffraction method. The antitumour activity of the synthesized complexes against ovarian and colorectal cancer models have been investigated. One of the synthesized complexes has shown moderate anticancer activity with lower resistance factor value against ovarian cancer model compared to clinical standard cisplatin. Another complex displayed promising antibacterial activity against Staphylococcus aureus .